PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT MATAHARI DEPARTMENT STORE PEJATEN VILLAGE - Munir Azhari (Sekolah Tinggi Manajemen IMMI Jakarta, 2019)
Munir Azhari, Analysis of the Influence of Service Quality on Customer Satisfaction at Matahari Department Store in Pejaten Village, Jakarta. In this era, the quality of the services offering has full attention for companies. Moreover,it’s can be use as a tool to achieve competitive advantage. Marketing is a social and managerial by which individuals and group obtain what they need what through creating, offering and exchanging product of value of with other. Customer satisfaction is defined as an evaluation that provides results where the experience in accordance with the as expected. Service quality is a term which describes a comparison of expectations with performance. Quantitative methods emphasize objective measurements and the statistical, mathematical, or numerical analysis of data collected through polls, questionnaires, and surveys, or by manipulating pre-existing statistical data using computational techniques. The resulted of Linear Regression Analysis show that the linear regression equation values are as follows: Y = 18.908 + 0.649 X and Y = customer satisfaction, X = service quality. The value of R Square (coefficient of determination) is 44.9%. Which means the influence of service quality variables (X) on customer satisfaction (Y) is 44.9%. Based on the results of the t test, the results of this study resulted in t 6.873 t table 2.002 so that it can be concluded that that X variable influence of on Y variable.